Proposed Potential Security Infrastructure in VANETS using Tamper Registered Hardware - Shaik Mahaboob Jani; Syed Umar (International Journal of Electrical and Computer Engineering (IJECE), 2016)
All over the world many road accidents are occurred due to lack of knowledge of vehicle`s distance and speed. But this issue will be solved by using VANETS through which we can well know about the speed of the vehicle and how much distance it is from other vehicles in all sides. So the VANETS will play a very crucial role in the safety and mostly avoidance of accidents like reacting immediately in dangerous situations. In order to prevent the abuse of VANETS a potential security infrastructure is needed to maintain confidential requirements like message integrity & availability. To achieve this we have proposed a concept called A seperate Potential security infrastructure facilitated with symmetric & Asymmetric cryptography with TRH. Our proposed theory will give very high efficient in terms of Computational Needs for the VANETS users.